Investigating Mechanical Properties of Metakaolin-Based Geopolymer Concrete Optimized with Wastepaper Ash and Plastic Granules - Khaleel Midhin, Midhin A.; Wong, Leong Sing (Civil Engineering Journal, 2024)
This study develops an environmentally friendly geopolymer concrete (GPC) using wastepaper ash (WPA) and high-density polyethylene (HDPE) granules, addressing environmental challenges such as wastepaper and HDPE disposal and CO2emissions from cement production. WPA was produced by incinerating wastepaper at 550 °C for one hour and used as a partial replacement for MK in ratios of 10%, 20%, 30%, 40%, 50%, and 100%, while HDPE granules replaced river sand in ratios from 1% to 5%. The results showed that the use of 30% WPA resulted in a compressive strength (CS) of 35.38 MPa, which was significantly higher than the control sample's CS of 31.62 MPa. The use of 30% WPA increased slump due to lower water demand. The combination of 3% HDPE and 30% WPA further enhanced the mechanical properties, resulting in a CS of 36.54 MPa, representing a 15.5% increase over the control. However, the addition of 3% HDPE and 30% WPA reduced the slump, attributed to the increased friction from the HDPE granules. Advanced analyses, including SEM, EDX, and XRD, confirmed a refined pore structure and increased geopolymerization in the treated GPC. It is novel to optimize WPA and HDPE as waste products in the production of MK-based GPC. Doi: 10.28991/CEJ-SP2024-010-011 Full Text: PDF